The impact of COVID-19 on elective and trauma spine service in a district general hospital. (2020) - Zahra, Wajiha; Karia, Monil; Rolton, Daniel
Abstract : Aims: The aim of this paper is to describe the impact of COVID-19 on spine surgery services in a district general hospital in England in order to understand the spinal service provisions that may be required during a pandemic. Methods: A prospective cohort study was undertaken between 17 March 2020 and 30 April 2020 and compared with retrospective data from same time period in 2019. We compared the number of patients requiring acute hospital admission or orthopaedic referrals and indications of referrals from our admission sheets and obtained operative data from our theatre software. Results: Between 17 March to 30 April 2020, there were 48 acute spine referrals as compared to 68 acute referrals during the same time period last year. In the 2019 period, 69% (47/68) of cases referred to the on-call team presented with back pain, radiculopathy or myelopathy compared to 43% (21/48) in the 2020 period. Almost 20% (14/68) of spine referrals consisted of spine trauma as compared to 35% (17/48) this year. There were no confirmed cases of cauda equine last year during this time. Overall, 150 spine cases were carried out during this time period last year, and 261 spine elective cases were cancelled since 17 March 2020. Recommendations: We recommend following steps can be helpful to deal with similar situations or new pandemics in future: 24 hours on-call spine service during the pandemic. Clinical criteria in place to prioritize urgent spinal cases. Pre-screening spine patients before elective operating. Start of separate specialist trauma list for patients needing urgent surgeries. Conclusion: This paper highlights the impact of COVID-19 pandemic in a district general hospital of England. We demonstrate a decrease in hospital attendances of spine pathologies, despite an increase in emergency spine operations. Cite this article: Bone Joint Open 2020;1-6:281–286.